EFISIENSI PENGGUNAAN BANGSAL PADA MASA PANDEMI COVID-19 DENGAN MENGGUNAKAN STANDAR BARBER JOHNSON - Siti Lailatul Lutfiah; Sali Setiatin (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2021)
Hospitals are part of a cooperation of health services to achieve health performance indicators set by the regions. In improving the quality of hospital services, it requires an increase in good supporting facilities including bed management. Based on observations conducted at RSUD Cililin, it shows that the use of beds before and during the COVID-19 pandemic has not been efficient. So that the hospital needs to evaluate the optimal use of beds.The purpose of this study was to determine and identify the significant effect of the Barber Johnson Chart on the efficiency of bed use and management at RSUD Cililin.This research method uses quantitative research with a descriptive approach. The subjects of this study included the reporting section and the head of the medical record. The object of this research is the in-patient register book. Research data collection techniques are by interviews and observations.Based on the results of the study, it is known that the average BOR value is 46,73%. The AVLOS value is 3, while the average TOI value is 4,98. The average BTO value is 14,14.Keywords: Efficiency, bed, covid-19 pandemic, barber Johnson